2019
DOI: 10.1111/ijac.13157
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures and mechanical properties of Cf/LAS composite and Ti60 alloy joints brazed with TiZrNiCu + Cf mixed powders

Abstract: In this paper, carbon fiber reinforced lithium aluminosilicate (LAS) glass‐ceramics matrix composites (Cf/LAS composites) are joined to Ti60 alloy using TiZrNiCu + Cf mixed powders by proper process parameters. The carbon fibers distribute uniformly in the brazing interlayer and react with Ti, Zr elements in the brazing alloy to form (Ti, Zr)C thin reactive layers, which are between the carbon fibers and the Ti, Zr elements. The effect of Cf content on the mechanical properties and microstructure of brazed joi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The increase in shear strength from 47.3 MPa to 73.5 MPa was reported with the 0.3% addition of C f filler in braze alloy powder. The increase in the joint strength was ascribed to the crack propagation through the composite interlayer instead of interface near the C f [288].…”
Section: Other Applicationsmentioning
confidence: 99%
“…The increase in shear strength from 47.3 MPa to 73.5 MPa was reported with the 0.3% addition of C f filler in braze alloy powder. The increase in the joint strength was ascribed to the crack propagation through the composite interlayer instead of interface near the C f [288].…”
Section: Other Applicationsmentioning
confidence: 99%
“…Many methods, such as adhesive joining, 4 solid‐state bonding, 5 and brazing, 6‐9 have been developed for joining ceramics to itself or metals (alloys). Among these methods, brazing is suitable to obtain reliable ceramics/ceramics (or metal) metallurgical joints due to its simplicity, convenience, low cost, and high joint strength 10‐12 …”
Section: Introductionmentioning
confidence: 99%
“…Mittal et al found that Cu doped ZnO nanoparticles show a shift of both excitation and emission spectra to the visible region compared with pure ZnO. Xia et al found that ZnO nanoparticles doped with Cu show a narrowing of the optical band gap. Ba‐Abbad et al found that Fe‐doped ZnO nanoparticles show a smaller crystal size and lower band gap as well as better absorption in the visible light region in comparison with the un‐doped ZnO.…”
Section: Introductionmentioning
confidence: 99%